Global Halal Market : the position of Malaysia as halal food producer / Ahmad Naif Ilmam Mohd Nawawi - Mohd Nawawi, Ahmad Naif Ilmam (Academy of Contemporary Islamic Studies (ACIS), 2018)
Halal product is the most important part in daily life especially for Muslim. As we know, the number of Muslims increase day by day and demand to the halal products also gain up through the year. This kind of situation effects the production of halal product, especially in food industries because people nowadays know the important of halal food and the suppliers will increase their production in order to fulfil the demand. Allah s.w.t mentions in the Holy Quran about halal in surah Al-Baqarah in verse 168 that told to us to eat the lawful and good things out of the earth and not follow the footsteps of Shaitan. Nowadays, halal sectors become a part of the demand in Muslim daily life. Then halal products especially halal foods have also penetrated the global market. Malaysia is one of the exporters of halal food and products to other countries. But, how far is Malaysia's position in halal global market? Thus, this study is done with intend of reviewing the global halal market position as well as Malaysia's position as a producer of halal products and food in the global market.